Complement inhibitors from scabies mites promote streptococcal growth--a novel mechanism in infected epidermis? - Angela Mika; Simone L Reynolds; Darren Pickering; David McMillan; Kadaba S Sriprakash; David J Kemp; Katja Fischer (Public Library of Science (PLoS), 2012)
BACKGROUND: Scabies is highly prevalent in socially disadvantaged communities such as indigenous populations and in developing countries. Generalized itching causes discomfort to the patient; however, serious complications can occur as a result of secondary bacterial pyoderma, commonly caused by Streptococcus pyogenes (GAS) or Staphylococcus aureus. In the tropics, skin damage due to scabies mite infestations has been postulated to be an important link in the pathogenesis of disease associated with acute rheumatic fever and heart disease, poststreptococcal glomerulonephritis and systemic sepsis. Treatment of scabies decreases the prevalence of infections by bacteria. This study aims to identify the molecular mechanisms underlying the link between scabies and GAS infections. METHODOLOGY/PRINCIPAL FINDINGS: GAS bacteria were pre-incubated with blood containing active complement, phagocytes and antibodies against the bacteria, and subsequently tested for viability by plate counts. Initial experiments were done with serum from an individual previously exposed to GAS with naturally acquired anti-GAS antibodies. The protocol was optimized for large-scale testing of low-opsonic whole blood from non-exposed human donors by supplementing with a standard dose of heat inactivated human sera previously exposed to GAS. This allowed an extension of the dataset to two additional donors and four proteins tested at a range of concentrations. Shown first is the effect of scabies mite complement inhibitors on human complement using ELISA-based complement activation assays. Six purified recombinant mite proteins tested at a concentration of 50 µg/ml blocked all three complement activation pathways. Further we demonstrate in human whole blood assays that each of four scabies mite complement inhibitors tested increased GAS survival rates by 2-15 fold. CONCLUSIONS/SIGNIFICANCE: We propose that local complement inhibition plays an important role in the development of pyoderma in scabies infested skin. This molecular link between scabies and bacterial infections may provide new avenues to develop alternative treatment options against this neglected disease.